THE EFFECT OF MODEL SCIENTIFIC INQUIRY USING MEDIA PhET TOWARD SKILLS PROCESS OF SCIENCE VIEWED FROM CRITICAL THINKING SKILLS - Nanda Safarati (Universitas Negeri Medan, 2017)
The purpose of research to analyse: the science process skills that are taught in a model of scientific inquiry using the media PhET better than students taught by learning direct instruction, science process skills of physics students who has the critical thinking skills using a model of scientific inquiry than average -rata better than students who have critical thinking skills using a direct model of instruction above average, the interaction of scientific inquiry learning model using PhET media with critical thinking skills of students in improving students' science process skills. This research is quasi experimental. Technique that used to gain a sample is random cluster sampling. The instrument used is the science process skills test and test critical thinking skills. The results of this study concluded that: the science process skills of students who are taught by the model of scientific inquiry using the media PhET better than students taught by learning direct instruction, science process skills of physics students who have the critical thinking skills using a model of scientific inquiry over average better than students who have critical thinking skills using a direct model of instruction above average, there is interaction scientific inquiry model using the media PhET with critical thinking skills of students in improving students' science process skills.